Assessment of ambient noise levels in the intensive care unit of a university hospital - Hatem O Qutub; Khaled F El-Said (Wolters Kluwer Medknow Publications, 2009)
Background:Noise is recognized as a source of hazard to the patient's environment. Studies have also shown that it has a direct impact on mortality and morbidity as a result of sleep deprivation which affects the immunity of critically ill patients. Objectives: The aim of this study was to measure levels of environmental noise in a six- bed, open-plan general medical intensive care unit (MICU). Methods: Levels of exposure to environmental noise were assessed in the intensive care unit of King Fahad Hospital of the University (KFHU) where measurements of environmental noise were taken using calibrated sound level meter during shifts of working days and weekends. Results : Statistical analysis revealed that there were no significant differences between noise levels in the morning, evening and night shifts of working days and weekends in the ICU of KFHU (p value =0.155, 0.53 and 0.711) respectively . There was no significant difference between overall level of exposure to noise in the working days and weekends as well (p-value=0.71). However, the assessed levels of exposures to noise were still higher than stipulated international standards. Conclusion : Some sources of environmental noise, such as the use of oxygen, suction equipment or respirators are unavoidable. Nevertheless, hospital ICUs should have measures to minimize the level of exposure to noise in the ICU. Further research in this area might focus on the noise level and other modifiable environmental stress factors in the ICU that affect patients as well as the staff.